2000
DOI: 10.1002/lt.500060109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virologic outcomes of hepatitis B and C viral coinfection after liver transplantation: Effect of viral hepatitis D

Abstract: Hepatitis B (HBV) and C viral (HCV) dual-infectionassociated liver disease is an uncommon indication for liver transplantation. The clinical and virologic outcomes in such patients have not been well studied. We retrospectively studied 13 patients with hepatitis B surface antigen (HBsAg) and antibody to HCV positivity who underwent orthotopic liver transplantation (OLT) and survived at least 30 days post-OLT. Antibody to hepatitis delta virus (HDV) was negative in 8 patients (group I) and positive in 5 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Survival rate has been shown to be up to 90% at 5 years in these patients, though no dedicated studies have been done in patients concomitantly infected with HIV. 26 Interestingly, in a study of a small cohort of liver-transplant recipients the presence of HDV may have inhibited HCV replication and recurrence in patients who were coinfected with hepatitis B, D, and C. 27 HDV, however, may persist despite adequate HBV suppression. A recent study of viral kinetics following liver transplantation demonstrated positive HDAg staining in transplanted livers in the absence of liver HBV DNA/covalently closed circular DNA, suggesting the possibility of latent HDV following liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rate has been shown to be up to 90% at 5 years in these patients, though no dedicated studies have been done in patients concomitantly infected with HIV. 26 Interestingly, in a study of a small cohort of liver-transplant recipients the presence of HDV may have inhibited HCV replication and recurrence in patients who were coinfected with hepatitis B, D, and C. 27 HDV, however, may persist despite adequate HBV suppression. A recent study of viral kinetics following liver transplantation demonstrated positive HDAg staining in transplanted livers in the absence of liver HBV DNA/covalently closed circular DNA, suggesting the possibility of latent HDV following liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The only patient who was not reinfected with HCV was a patient with a triple infection with HBV, HCV, and hepatitis D virus, who had undetectable HBV and HCV plasma load before transplantation. The suppressive effect of hepatitis D virus on HCV and HBV replication has been described in patients with dual or triple viral infection, and persists after transplantation 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…Another option for patients with triple infection involving HBV, HCV and HDV is liver transplantation. Risk of recurrence of HBV and HCV is decreased in transplanted liver which otherwise may occur due to viral interference phenomenon [73]. Treatment options for triple infection involving HBV, HCV and HDV are very limited.…”
Section: Literature Searchmentioning
confidence: 99%
“…Treatment options for triple infection involving HBV, HCV and HDV are very limited. There is no optimal treatment for this up to now [73]. For selecting most appropriate antiviral treatment of triple infection, patient should be monitored carefully and virological assessment should be carried out to determine dominant virus.…”
Section: Literature Searchmentioning
confidence: 99%